PEDAGOGICAL EXPERIMENT FOR VERIFICATION OF EFFICIENCY OF THE METHODICAL SYSTEM OF ORGANIZATION OF THE ALGORITHMIC TESTING IN THE PROCESS OF PREPARATION OF FUTURE TEACHERS OF MATHEMATICS (Journal of Information Technologies in Education (ITE), 2010)
Aims and maintenance of the basic stages of pedagogical experiment are described in the article, on the basis of what a conclusion about efficiency of the offered methodical system of organization of the algorithmic testing in the process of preparation of future teachers of mathematics is done. For control of knowledge on algorithmization drawn on programmatic a methodical complex the Integrated environment of study of course of «Basis of algorithmization and programming» (http://weboap.ksu.ks.ua), developed in the laboratory of the integrated environments of teaching of RIIT of the Kherson state university.
Keywords: algorithmic testing; computer-integrated environment; control of knowledge; methodical system; pedagogical experiment